Long-term effects of manure and chemical fertilizers on soil antibiotic resistome. (July 2018) - Xie, Wan-Ying; Yuan, Shuang-Ting; Xu, Ming-Gang; Yang, Xin-Ping; Shen, Qi-Rong; Zhang, Wen-Wen; Su, Jian-Qiang; Zhao, Fang-Jie
Abstract: Applications of manure and chemical fertilizers can significantly modulate the bacterial communities in soil, but the effects on the soil antibiotic resistome and the underlying mechanisms remain largely unclear. In the present study, antibiotic resistance genes (ARGs) and bacterial communities were characterized using high-throughput quantitative PCR and Illumina HiSeq sequencing, respectively, in soils from a long-term (25 years) field experiment. Treatments included no fertilizers (control), chemical fertilizers (NPK), NPK with straw return (NPKS), pig manure (M), and M with chemical fertilizers (NPKM). Both NPK and NPKS decreased soil pH and induced a substantial shift in the bacterial communities, but had only moderate effect on the ARG diversity and abundance. The effect of straw return was hindered by the dominant influence of NPK. In comparison, additions of pig manure (M and NPKM) maintained the diversity of bacterial community and significantly influenced the ARG profiles by introducing extra ARGs from pig manure and boosting the soil indigenous ARG members. Manured soils harboured clusters of ARGs and transposase genes which were relatively independent of bacterial phylogenetic lineages, suggesting a strong co-occurrence of ARGs in soil bacteria which may result from horizontal gene transfers (HGT). Our results indicate the importance of HGT in the maintenance of ARG composition in agricultural soils, especially those receiving long-term manure applications. Highlights: Pig manure applications greatly increased ARG diversity and abundances. Chemical fertilizer applications impacted bacterial community but had limited effect on ARG profile. Manure introduced extra ARGs and stimulated the indigenous ARGs. ARGs form clusters independent of bacterial phylogeny in manured soils.